‘Mera Gaon, Mera Gaurav’ policy: A source of hypothesis for the co-production of adaptive agricultural knowledge - SINGH, RANJAY K; SINGH, ANSHUMAN; SHEORAN, PARVENDER; SHARMA, D K; SHARMA, P C (The Indian Journal of Agricultural Sciences, 2019)
Over the past few decades, Indian agriculture is increasingly confronting a range of social, economic and ecological challenges putting the livelihood security of millions of resource poor farmers at risk. The ills plaguing the farm sector have received critical policy attention leading to the launch of several farmer-centric policies and programs aimed at infusing resilience into the ailing croplands, making agriculture a remunerative activity and for driving the rural poor out of poverty. One such initiative called 'Mera Gaon, Mera Gaurav' (My Village, My Pride) was launched in 2015 with the goal of revolutionizing the pace of technology transfer to the farmers' doorsteps in a time bound manner. In this article, we propose a new model consisting of five propositions for improving the modus operandi of 'Mera Gaon, Mera Gaurav'program such that it does not merely remain a tool of technology dissemination but instead serves as a viable platform for the co-production of agricultural knowledge which is more sustainable, inclusive and compatible to resolving the current and emerging agricultural issues.